Nano-selenium strengthens potato resistance to potato scab induced by Streptomyces spp., increases yield, and elevates tuber quality by influencing rhizosphere microbiomes - Liu, Haixu; Zhang, Yan; Zhang, Lili; Liu, Yingjie; Chen, Yufei; Shi, Ying (Frontiers in Plant Science, 2025)
IntroductionThe application of selenium could directly or indirectly modulate the activity of antioxidant enzymes in crops, thereby mitigating the detrimental effects of abiotic and biotic stresses on crop health. However, there are few studies on the effects of nano-selenium fertilizer on potato scab caused by Streptomyces spp., potato yield and tuber quality.MethodsWe aimed to elucidate the impact of nano-selenium fertilizer on potato disease resistance, yield, tuber quality, antioxidant enzyme activity and rhizosphere soil bacterial communities, and to determine the optimal frequency and growth stages of nano-selenium fertilizer spraying.Results and discussionThe application of nano-selenium fertilizer twice during the seedling stage significantly reduced the disease index of potato scab, enhanced potato yield, tuber quality (dry matter, Vitamin C, crude protein, and selenium content), and antioxidant enzyme activity (glutathione peroxidase, peroxidase, polyphenol oxidase, superoxide dismutase, and phenylalanine ammonia lyase). The diversity of the rhizosphere bacterial community of potatoes subjected to selenium fertilizer spraying at the seedling stage increased significantly, and concurrently, the symbiotic network of rhizosphere bacterial microbiome grew more complex. Beneficial microorganisms such as bacteria of the genus Bacillus were enriched in the rhizosphere soil. The current study provided theoretical support for the exploration of a potato selenium-enriched technology system and supplies scientific guidance for the utilization of nano-selenium.